Bisacurone attenuates diabetic nephropathy by ameliorating oxidative stress, inflammation and apoptosis in rats. (26th November 2022) - Yang, F; Zhang, Z; Zhang, L
Background: Diabetes nephropathy (DN) is a serious diabetic problem that may progress to renal failure. The root of Curcuma longa L., often known as turmeric, provides various health benefits. Bisacurone is a bioactive terpenoid found in small amounts in turmeric that possesses anti-inflammatory and antioxidant properties. The present study focuses on the potential protective effects of bisacurone against DN via reducing renal inflammation, oxidative stress, and apoptosis. Methods: Type 2 diabetes was created in rats by feeding them a high-fat/high-sugar diet for 8 weeks, followed by a low dose of streptozotocin and Bisacurone (50 and 100 μg/kg bisacurone) given for 4 weeks. Results: In diabetic rats, bisacurone reduced hyperglycemia, protected against body weight (BW) loss, lowered renal markers, reduced lipid profile alterations and avoided histological abnormalities. Bisacurone treatment reduced oxidative stress by decreasing malondialdehyde (MDA) levels while enhancing antioxidant defenses through superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) levels. Furthermore, bisacurone treatment activated the renal Nrf2/Keap1 signaling pathway but attenuated the high levels of NFκB p65, TNF-α, IL-1β, IL-6, Cox2, and iNOS. Bisacurone also reduced Bax, caspase-3, caspase-9 and cytochrome c but increased Bcl-2 in the kidneys of diabetic rats. Conclusion: In the present study, bisacurone reduces DN by reducing hyperglycemia, oxidative stress, inflammation, and apoptosis, while also increasing Nrf2/HO-1 signaling.